DESIGN AND OPTIMIZATION OF BRAKE CALIPER MOUNT ADAPTER FOR METROKAPSUL - Muhammad Judawisastra, Naufal
Metrokapsul is a public transportation which is categorized in Automated People Mover transportation mode and it is being developed by PT. TReKKa. In order to assure the safety of Metrokapsul operation, analysis of the components on its braking system has to be done. Brake caliper mount adapter is a component of braking system. This component is essential that it helps to rigidly attach the brake caliper to the steering knuckle. In common vehicles, brake caliper usually matches with the steering knuckle. However, Metrokapsul braking system is unique and needs brake caliper mount adapter which has to be custom manufactured. The purpose of this research is to find out an optimum design of brake caliper mount adapter under the maximum braking condition. Moreover, the maximum stress and safety factor of the brake caliper mount adapter are obtained. The safety factor of the adapter is determined based on the Regulation of the Minister of Transportation No 175 of 2015. Finite element analysis will be conducted to study the effect of the static loading and to determine the maximum stress on the design and the bolts. In addition, topology optimization will be conducted to generate an optimum design of the brake caliper mount adapter. The maximum braking force needed by the Metrokapsul is 26,045.74 N. The optimum design of the brake caliper mount adapter shows the maximum stress of 190.12 MPa and the safety factor of 1.35. The optimization delivers the mass reduction of 30% whereas the maximum stress is reduced by 9.84%.